ANALISIS POTENSI PENDAPATAN PAJAK HIBURAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN PAJAK DAERAH (Studi Pada Dinas Pendapatan Kabupaten Tulungagung Tahun 2012-2014) - Firmansyah, Asrul (Jurnal Mahasiswa Perpajakan, 2016)
Development of places of entertainment in Tulungagung that can increase revenue in Tulungagung in particular especially from entertainment tax sector. This study aims to know the amount of potential tax revenues entertainment, the effectiveness of tax collection in Tulungagung entertainment and amusement determine the contribution of tax revenue to the Local Tax Tulungagung The results show that the potential tax revenues entertainment in Tulungagung years 2012-2014 still greater than the target amount and the actual amount of tax revenues entertainment. The effectiveness of the entertainment tax years 2012-2014 has always been above 100% but tend to fluctuating the Entertainment tax income contribution of the local tax revenue Tulungagung always categorized as lacking during the years 2012-2014. The largest contribution in 2013 is 1.75%.Regional Revenue Office Tulungagung should direct observation on a regular basis against the organizers of entertainment venues and improve socialization to the organizers of the new entertainment venues to meet his tax obligations Keywords : Potential, Entertainment Tax, Contributions ABSTRAK Berkembangnya tempat-tempat hiburan di Tulungagung merupakan hal yang dapat meningkatkan pendapatan asli daerah di Tulungagung khususnya dari sektor pajak hiburan. Â Penelitian ini bertujuan untuk Mengetahui jumlah potensi pendapatanÂ  pajak hiburan, efektifitas pemungutan pajak hiburan di Tulungagung serta mengetahui kontribusi pendapatan pajak hiburan terhadap Pajak Daerah Tulungagung Efektivitas pajak hiburan tahun 2012-2014 selalu berada diatas 100% namun cenderung fluktuatif. Kontribusi pendapatan pajak hiburan terhadap pendapatan pajak daerah Tulungagung selama tahun 2012-2014 selalu termasuk kategori sangat kurang. Kontribusi terbesar pada tahun 2013 yaitu sebesar 1,75%.. Dinas Pendapatan Daerah Kabupaten Tulungagung sebaiknya melakukan pengamatan langsung secara berkala terhadap para penyelenggara tempat hiburan serta meningkatkan sosialisasi kepada para penyelenggara tempat hiburan baru untuk memenuhi kewajiban pajaknya Kata kunci : Potensi, Pajak Hiburan, Kontribusi